2002
DOI: 10.1076/ejom.40.4.235.16690
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure of Apical Vesicles of Tuft Cells in the Main Excretory Duct of the Rat Submandibular Gland

Abstract: Tuft cells are present in the mucosal epithelium of a number of hollow organs including the main excretory duct (MED). Despite their distinctive features such as the long, thick, blunt microvilli with prominent rootlets and the large number of vesicles in the apical cytoplasm, the hypolemmal terminal-tuft cell relationship and the true form of the various vesicles and tubules are still controversial. The present study investigated the above mentioned features of tuft cells in the MED of rat submandibular gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…It has been suggested that these molecular complex may form a tubulovesicular network made of structural proteins such as citokeratin 18, fimbrin, and villin 26 . However, attempts to render the volumetric ultrastructure of the network have lacked sufficient Z resolution to prove the existence of a network 11 . These tubular network was also evident in our SBEM and ATUM images (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that these molecular complex may form a tubulovesicular network made of structural proteins such as citokeratin 18, fimbrin, and villin 26 . However, attempts to render the volumetric ultrastructure of the network have lacked sufficient Z resolution to prove the existence of a network 11 . These tubular network was also evident in our SBEM and ATUM images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the cells also have “lateral microvilli” but the purpose is unclear 10 . At the base of the microvilli tuft, there is a prominent cluster of vesicles and caveoli, which has been suggested to form a network but the evidence is inconclusive 11 . Since tuft cells were first reported, about a third of the published articles have focused on their ultrastructure and provided evidence of at least five peculiar features.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations